Application of engineered extracellular vesicles to overcome drug resistance in cancer - Nonaka, Taichiro (Frontiers in Oncology, 2022)
Targeted therapies have significantly improved survival rates and quality of life for many cancer patients. However, on- and off-target side toxicities in normal tissues, and precocious activation of the immune response remain significant issues that limit the efficacy of molecular targeted agents. Extracellular vesicles (EVs) hold great promise as the mediators of next-generation therapeutic payloads. Derived from cellular membranes, EVs can be engineered to carry specific therapeutic agents in a targeted manner to tumor cells. This review highlights the progress in our understanding of basic EV biology, and discusses how EVs are being chemically and genetically modified for use in clinical and preclinical studies.